2013
DOI: 10.3389/fnbeh.2013.00042
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Neural and Behavioral Consequences for Unitizing Emotional and Neutral Information

Abstract: A special type of association, called a “unitization,” is formed when pieces of information are encoded as a single representation in memory (e.g., “shirt” and “blue” are encoded as a “blue shirt”; Graf and Schacter, 1989) and typically are later reactivated in memory as a single unit, allowing access to the features of multiple related stimuli at once (Bader et al., 2010; Diana et al., 2011). This review examines the neural processes supporting memory for unitizations and how the emotional content of the mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 143 publications
(208 reference statements)
0
33
0
Order By: Relevance
“…Our results are compatible with this view in that item and associative memory were affected in opposite directions. Speculatively, negative emotion might enhance item memory through amygdaladependent processes and modulation of other MTL structures, such as perirhinal cortex (for similar views, see Mather 2007;Murray and Kensinger 2013). In further support of this link, a recent study in rodents demonstrates a potential role for the amygdala in recognition memory, with damage to this structure found to reduce familiarity-type recognition of nonemotional items, while recollection-type processes were spared (Farovik et al 2011).…”
Section: Discussionmentioning
confidence: 68%
“…Our results are compatible with this view in that item and associative memory were affected in opposite directions. Speculatively, negative emotion might enhance item memory through amygdaladependent processes and modulation of other MTL structures, such as perirhinal cortex (for similar views, see Mather 2007;Murray and Kensinger 2013). In further support of this link, a recent study in rodents demonstrates a potential role for the amygdala in recognition memory, with damage to this structure found to reduce familiarity-type recognition of nonemotional items, while recollection-type processes were spared (Farovik et al 2011).…”
Section: Discussionmentioning
confidence: 68%
“…These subprocesses are often thought to be the core components of recognition memory (Aggleton and Brown, 1999;Düzel et al, 1999;Mandler, 1980;Mecklinger, 2000;Rugg and Curran, 2007;Yonelinas, 1994;Yonelinas and Parks, 2007) and the question whether emotions can differentially modulate them is not fully settled . Some studies have found that emotion can enhance "source memory" performance (Croucher et al, 2011;D'Argembeau and Van der Linden, 2005;Doerksen and Shimamura, 2001;Murray and Kensinger, 2013). These results suggest that emotion can modulate recollection processes, given that source memory tasks require participants to retrieve information belonging to the context in which a central item has been encoded (Koenig and Mecklinger, 2008;Wilding andRugg, 1996, 1997;Yick and Wilding, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…The quadratic effect of shock probability on recollection could also be explained on the basis of studies showing an association between emotional arousal and hippocampusdependent memory dysfunctions (e.g. Murray and Kensinger, 2013;Murty et al, 2011). They suggest that in a state of high emotional arousal (i.e.…”
Section: Figurementioning
confidence: 99%